2001
DOI: 10.1074/jbc.m104787200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ligand-binding Site III on the Immunoglobulin-like Domain of the Granulocyte Colony-stimulating Factor Receptor

Abstract: The granulocyte colony-stimulating factor receptor (G-CSF-R) forms a tetrameric complex with G-CSF containing two ligand and two receptor molecules. The Nterminal Ig-like domain of the G-CSF-R is required for receptor dimerization, but it is not known whether it binds G-CSF or interacts elsewhere in the complex. Alanine scanning mutagenesis was used to show that residues in the Ig-like domain of the G-CSF-R (Phe 75 , Gln 87 , and Gln 91 ) interact with G-CSF. This binding site for G-CSF overlapped with the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
1
37
0
1
Order By: Relevance
“…Then, the CBD of some large-size cytokine receptors (gp130, IL-12R␤1, and granulocyte-colony stimulating factor) interact with the cytokine(s) through site II (57,(61)(62)(63)(64). Recruitment of an additional site of interaction (site III) located on the Ig-like domain of a second large-size receptor leads to oligomerization and signaling of the receptor complex (65)(66)(67)(68)(69). Because no Ig-like domain is present in GPL, we can hypothesize that GPL should interact with its potential ligand(s) through a site II or a site I. GPL also likely implicates a neighbor receptor holding an Ig-like module to define the site III and to allow the dimerization process of large-size signaling subunits and subsequent signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the CBD of some large-size cytokine receptors (gp130, IL-12R␤1, and granulocyte-colony stimulating factor) interact with the cytokine(s) through site II (57,(61)(62)(63)(64). Recruitment of an additional site of interaction (site III) located on the Ig-like domain of a second large-size receptor leads to oligomerization and signaling of the receptor complex (65)(66)(67)(68)(69). Because no Ig-like domain is present in GPL, we can hypothesize that GPL should interact with its potential ligand(s) through a site II or a site I. GPL also likely implicates a neighbor receptor holding an Ig-like module to define the site III and to allow the dimerization process of large-size signaling subunits and subsequent signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…CNTF, CLC, IL-6, and IL-11) binds to this co-receptor (CNTFR, IL-6R, and IL-11R) through binding site I (C-terminal parts of the AB loop and of helix D (8,20,26,(33)(34)(35)(36)). The glycoprotein gp130 interacts through binding site II, located on the solvent-exposed faces of helices A and C (3,37,38). These sites are similar to binding sites I and II of the growth hormone (32).…”
mentioning
confidence: 94%
“…This is consistent with the much smaller free energy of binding observed for the second interacting receptor in the high affinity complex (LIFR binding to the OSM⅐gp130 complex) than for the first interacting receptor (LIFR binding to LIF or CT-1). In a study aimed to find the binding epitope of the Ig-like domain of G-CSF receptor, Layton et al (37) observed that single mutations in the Ig-like domain of the granulocyte-colony stimulating factor receptor did not impair binding or biological activity but that double mutations were required to observe an effect. They explained this behavior by the low additional change in free energy upon the second receptor binding, which should be shared by several residues at the interface, corresponding to weak interactions.…”
Section: Lif Binding Site Of Lifr-mentioning
confidence: 99%
“…The aromatic ring of Tyr-39 in hGCSF exhibits a stacking interaction parallel to that of Phe-75 in hGCSF-R. Five hydrogen-bonding interactions also contribute to the site III interaction as shown in Table 1. In these residues, Glu-46 and Val-48 in hGCSF and Phe-75, Gln-87, and Gln-91 in hGCSF-R are reported to be important for ligand binding and biological function (16)(17)(18)20).…”
Section: Figmentioning
confidence: 99%